A lean and mean strategy: a data migration industrial study. Issue 2 (12th September 2013) - Razavian, Maryam; Lago, Patricia
SUMMARY Many companies have legacy assets to be integrated or modernized. Like today's software developments, migration projects are faced with steadily increasing demands for efficiency: migration has to be carried out faster, better, and cheaper. At the same time, migration complexity increases, and migration projects remain challenging despite the companies' extensive experience. To cope with such efficiency demands, companies need a well‐defined migration strategy. In previous work, we have defined such a migration strategy called lean and mean strategy. In this paper, following technical action research, we apply our migration strategy, and evaluate it, in two large industrial case studies in the field of data migration. The use of the strategy in our case studies reveals the benefits of lean and mean strategy for meeting the efficiency demands. Copyright © 2013 John Wiley & Sons, Ltd.